Management and Treatment of Chronic Hepatitis C in HIV Patients - Barreiro, Pablo; Vispo, Eugenia; Labarga, Pablo; Soriano, Vincent (Seminars in Liver Disease, 2012)
Progression to cirrhosis occurs faster whereas response to peginterferon/ribavirin therapy is lower in patients with chronic hepatitis C coinfected with human immunodeficiency virus (HIV), as compared with hepatitis C virus (HCV) monoinfected individuals. The use of antiretroviral therapy may ameliorate poor outcomes in HIV/HCV coinfected patients. However, in the best scenario peginterferon/ribavirin therapy provides cure to 30% of patients harboring HCV genotypes 1 or 4 and to 70% of HCV genotypes 2 or 3 carriers, a rate lower than that seen in HCV monoinfection. Moreover, a substantial proportion of HIV/HCV coinfected patients are not treated due to contraindications, or do not complete therapy due to serious adverse events, or just do not wish to receive such a poorly tolerated medication. For these reasons, the advent of direct acting antivirals (DAA) has been eagerly awaited for treating HIV/HCV coinfected patients. However, new challenges have arisen, including the potential for harmful drug interactions with antiretroviral agents, poor drug adherence due to polymedication, increased risk for selection of drug-resistant HCV mutants, and unaffordable coverage in an environment of economic constraints. The use of noninvasive tools to measure liver fibrosis (i.e., elastometry) and pharmacogenomics (testing for IL28B and perhaps ITPA polymorphisms), along with consideration of early viral kinetics to guide length and drugs needed could help to individualize and improve the cost effectiveness of therapeutic decisions using DAA in HIV-infected patients with chronic hepatitis C.
Keywords: hepatitis C; human immunodeficiency virus; HIV; interferon; ribavirin; direct acting antivirals; IL28B; telaprevir; boceprevir